Pengaruh Label Halal dan Media Sosial Terhadap Keputusan Pembelian Skincare dengan Religiusitas Sebagai Variabel Moderasi - AzzaidaNaura Amalia; Imam Sopingi; Peni Haryanti; Athi’ Hidayati (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
The increasing use of skincare products among university students has made halal labels and social media important factors in purchasing decisions. In addition, consumers' religiosity is assumed to influence the relationship between these factors and purchasing decisions. This study aims to analyze the influence of halal labels and social media on skincare purchasing decisions and the role of religiosity as a moderating variable among students of Universitas Hasyim Asy'ari Tebuireng Jombang. This research employed a quantitative approach using an inferential method through questionnaires distributed to students who use skincare products. The collected data were analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The results indicate that halal labels and social media influence students' skincare purchasing decisions. Halal labels increase consumers' confidence in selecting products that comply with Islamic values, while social media serves as an important source of information that shapes perceptions and purchase intentions. The study also found that religiosity strengthens the influence of halal labels on purchasing decisions but weakens the influence of social media on purchasing decisions. These findings imply that highly religious consumers tend to prioritize halal aspects over information obtained from social media when making purchasing decisions